Pengembangan Media Mind Map Berbasis Powerpointplex pada Materi Kingdom Animalia untuk Siswa Kelas X MIPA SMAN 1 Airpura - Anggraeni, Ika; Silvina, Rini; Hatchi, Itgo (Perspektif Pendidikan dan Keguruan, 2024)
Learning media is an important component in the teaching and learning process. The use of media in learning can generate new desires and interests, increase motivation and stimulation of learning activities. One media that is suitable for animal kingdom material is mind maps. Kingdom animalia has a lot of material and explanations and branches so it is suitable to be described using a mind map. This research is development research that uses 4-D, which consists of the define, design, develop and disseminate stages. The research subjects were students of SMAN 1 Airpura class X MIPA. This research data is primary data consisting of validation, teacher practicality, and student practicality. Validation and practicality data were analyzed in the form of percentages. Based on the research carried out, a PowerPoint-based mindmap based on Animal Kingdom material that is valid and practical was produced. The validation value of the Powerpointplex-based mindmap for the animal kingdom material developed was 88%. For the practicality test by the teacher on the PowerPoint-based mindmap, the animal kingdom material developed was very practical with a score of 94%. The practicality test by students in stage I (limited test) obtained very practical results with a score of 91% and for the stage II test (field test) the results were very practical with a score of 86%.